Strategic Leadership and Green HRM: A Comprehensive Review of Existing Literature - Willma Fauzzia; Budi Santoso; Eeng Ahman (Yayasan Edukasi Cakrawala Nusantara, 2025)
This study presents a comprehensive literature review on the relationship between strategic leadership and Green Human Resource Management (GHRM). Drawing from twenty Scopus-indexed articles, the review highlights that visionary leadership plays a key role in embedding sustainability into organizational culture, driving employee engagement, and fostering environmental innovation. The findings emphasize the importance of organizational learning, adaptability, and technology as enablers of successful GHRM implementation. Challenges such as limited managerial knowledge, employee resistance, and resource constraints are also discussed. This review offers insights for both scholars and practitioners, stressing the need for leadership commitment, cross-functional collaboration, and continuous learning in building sustainable organizations. Future research is encouraged to explore GHRM across diverse sectors and cultural settings.